Analisis Pemecahan Masalah Barisan dan Deret oleh Siswa Ditinjau dari Adversity Quotient - Fachruddin, Mohammad (Jurnal Pendidikan Matematika : Judika Education, 2024)
This study aims to describe the problem solving of the formation and review series of adversity quotient. The subjects of this study were 3 students of class XII of SMA Negeri 1 Ampibabo, namely AQ climbing type students, AQ campers type students and AQ quitters type students. The subjects in this study were selected based on the results of the adversity response profile (ARP) test and recommendations from mathematics teachers. This type of research is qualitative research with a descriptive approach. Data collection was carried out by written tests and interviews. The results of the study are explained based on the stages of Bransford & Stein's problem solving, namely identifying problems, determining goals, exploring possible strategies, anticipating outcomes and acting, and looking back and learning. The results of this study indicate that AQ Climbers type students are able to meet all stages of problem solving. AQ campers type students are able to meet 4 stages of problem solving. AQ quitters type students are only able to meet 2 stages of problem solving. Conclusion, Every student has different abilities in solving mathematical problems, As a teacher, it is important to pay more attention to Campers and Quitters students in helping them develop skills to check the correctness of problem solving and improve more appropriate problem solving strategies. Keywords: Problem solving, Sequences and Series, Adversity Quotient